Pengaruh Pendidikan Kesehatan Terhadap Kesiapan Masyarakat Dalam Tindakan Awal Stroke Akut: The Effect of Health Education on Community Readiness in Early Management of Acute Stroke - Ernawati, Ernawati; Ariani, Sri Purwanti; Indrayadi, Indrayadi; Yuhansyah, Yuhansyah; Nadia, Nur (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Acute stroke is a neurological emergency that requires prompt management, as delays can result in permanent brain damage and even death. In Kelayan Subdistrict, community knowledge regarding the signs, symptoms, and initial actions for acute stroke remains low, which increases the risk of delayed treatment. Therefore, health education is necessary to enhance community preparedness in recognizing and responding to stroke appropriately. This study aimed to analyze the effect of health education on community preparedness in providing initial actions for acute stroke in Kelayan Subdistrict. The study employed a pre-experimental one group pretest–posttest design involving intervention and control groups, with interventions including counseling, leaflets and posters, and demonstrations of the FAST method. Community preparedness was measured before and after the intervention using questionnaires on knowledge, attitudes, and skills. The results showed a significant increase in knowledge, attitudes, skills, and overall preparedness scores in the intervention group following the health education program (p < 0.001), whereas the control group showed no significant changes (p > 0.05). These findings indicate that health education effectively enhances the community’s ability to recognize stroke signs and symptoms and take timely and appropriate initial actions. In conclusion, health education effectively improves the preparedness of the Kelayan Subdistrict community in responding to acute stroke and is recommended to be implemented routinely as a promotive and preventive measure to support early detection and timely response to stroke at the community level.